Прематурна ретинопатија: скрининг и современа терапија - Татеши, Беким (Медицински факултет, УКИМ, Скопје, 2016)
Introduction: Retinopathy of prematurity (ROP) is vasoproliferative disease of immature retina in premature infants, which can lead to severe visual impairment or blindness in a small but significant percentage of these children. Objectives: The implementation of screening with a high risk is to define the inclusion criteria for risk population of premature infants; to evaluate the development of blood vessels in the retina in premature infants; to determine the percentage of children with active stage of ROP; to estimate the proportion of gestational age (GA) or birth weight (BW) and the percentage of ROP; to evaluate effects of laserphotocoagulation (LPC) in the development and progression of ROP; within the study to develop a standard protocol with recommendations for screening which will be applicable to the study population and to investigate the number of premature infants in this group who are treated with LPC. Material and Methods: In this retrospective study data of premature babies which followed in period from May 2009 to May 2014 were analyzed. This study included all premature infants which are divided in three groups. In group I, premature babies with birth weight of ≤1500 g and/or born gestational age of 30 weeks or less, selected infants with a birth weight between 1500 and 2000 g or gestational age of >30 weeks with anunstable clinical course and who have additional risk factors in the development (the recommendations of the American Academy of Ophthalmology - AAO) will be involved and group II, in which premature children with parameters beyond protocol AAO in cooperation with neonatologists, who had other risk factors for ROP will be included. A group of premature infants who developed the active form of ROP and was treated by LPC were formed as a third group. Results: During the test period of 5 years 1036 preterm infants were registered. From this cohort 764/1036 (72.37%) are included in group I and 272/1036 (26.30%) in II group. The average gestational age of group I was 31.7±2.1 and the average birth weight was 1555.9±280.61 g. In group II the average of gestational age was 34.0±1.1 and average birth weight was 2314.9±279.9 g. With laserfotocoagulation are treated 165 premature children with average gestational age 30.1±2.11 wееks and with an average birth weight of 1382.2 g. The average number of laser spots in the group treated with laserfotocoagulation is 1919.5, a minimum of 400 and maximum of 4700. In this group, ROP5 was found in 10 premature babies in one eye and 6 in both eyes. Conclusion: Retinopathy of prematurity is the most important common problem of pediatricians and ophthalmologists and is a major cause for blindness in children. Screening is performed in order to detect active premature retinopathy, which should be treated in time with laserphotocoagulation. Clearly defined guidelines on screening and monitoring are basic rules for treated of retinopathy of prematurity.
Докторска дисертација одбранета во 2016 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Весна Димовска Јорданова.
Keywords: screening for retinopathy of prematurity, indirect ophthalmoscopy, laserfotocoagulation